Research clusters and activities - Zuwairie, Ibrahim (Kolej Kejuruteraan, 2020)
College of Engineering is the most recently established academic division in Universiti Malaysia Pahang. The academic staff come from various faculties in UMP. Each of them has different specialisations and talents, which are extremely beneficial to shape the future of College of Engineering. Research clusters are multidisciplinary and organised based on the academic departments available in the college